Uji Kinerja Unit Mesin Pasteurisasi Tipe Kontinyu untuk Pengolahan Sari Buah Sirsak - Suparlan Suparlan; Uning Budiharti; Astu Unadi (The University of Lampung, 2019)
Soursop fruit is one of the horticultural products that are easily damaged after the maturation process. This fruit is generally consumed in the form of fresh ripe or juice. The quality of the fruit is also very diverse and at harvest time the amount is abundant so the selling price tend to be low. One alternative to increase the added value of soursop fruit which the quality is poor and to extend the shelf life can be done through processing into juice. This study aims to test the performance of continuous type pasteurizer unit which has been developed by the Indonesian Center for Agricultural Engineering research and Development (ICAERD) in the processing of soursop juice on a small scale industry. The pasteurizer unit consists of a mixer, pasturizer, holder, filler, and cup sealer. The process of soursop juice processing includes fruit bunching, skin peeling, burial, mixing and dilution of slurry, fruit juice pasturization, and packaging. The pasteurization process was done at 80 ºC for 5-10 minutes. The pasteurization temperature is achieved at pavor pressure on water heating tube of about 1.0-1,5 bar. Under these conditions the capacity of continuous type pasteurizer unit was 160 l/h. The resulting juice has a TPC content on days 0, 7, and 14 after storage was 4.8 x 102, 5.1 x 102, and 1.9 x 103 cfu/g, respectively. The heavy metal content of Cu and Pb were 0.63 and 0.29 ppm, respectively.Keywords: performance test, pasteurizer, continuous type, soursop juice processing, value added product.